Biological interactions with surface charge in biomaterials - Syed, Tofail A. M. (RSC nanoscience & nanotechnology, 2012)
When a biomaterial is placed inside the body, a biological response is triggered almost instantaneously. With devices that need to remain in the body for long periods, such interactions can cause encrustation, plaque formation and aseptic loosening on the surface. These problems contribute to the patient's trauma and increase the risk of death. Electrical properties, such as local electrostatic charge distribution, play a significant role in defining biological interactions, although this is often masked by other factors. This book describes the fundamental principles of this phenomenon before.